Optimum displacement profile for the direct displacement-based design of steel moment-resisting frames - Arab, Mohammadamin; Tajmir Riahi, Hossein; Daei, Maryam (Structures (Oxford), 2022)
The direct displacement-based design (DDBD) procedure is well established for designing reinforced concrete and steel moment-resisting frames (SMRFs). However, a limited number of researches is available on optimum DDBD of SMRFs. Furthermore, the nonlinear time-history analysis response of structures designed based on this procedure is inconsistent with its initial assumptions. Design displacement profile is one of the most essential and influential parameters in the DDBD method because it can impress other design parameters. In this paper, an optimum displacement profile is proposed to improve the results of the DDBD procedure via using the particle swarm optimization (PSO) algorithm. In this regard, nine SMRFs with a different number of stories have been designed using the DDBD procedure. Nonlinear time history analyses are performed for these frames using OpenSees software. The models are subjected to a set of 20 ground motion records. Then, PSO algorithm has been used to optimize the displacement profile of the DDBD procedure to achieve uniform drift distribution along with the height of the frames. Finally, based on regression analysis, the optimum design displacement profile for SMRFs with a different number of stories is formulated. The proposed equations show an average reduction of about 20% and 40% in steel usage and design base shear of the frames, respectively, while they have uniform drift along their heights.